2000
DOI: 10.2135/cropsci2000.40155x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Partial Resistance to Sclerotinia Stem Rot in Soybean

Abstract: portion of the resistance in the field is the result of physiological resistance or escape mechanisms. These Little is known about the inheritance of partial resistance in soyescape mechanisms could include flowering date, lodgbean [Glycine max (L.) Merr.] to sclerotinia stem rot, caused by the fungal pathogen Sclerotinia sclerotiorum (Lib.) de Bary. This ing, canopy architecture, and maturity, which have all information would be useful to soybean breeders who are developing been shown to be significantly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
132
2
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(153 citation statements)
references
References 16 publications
(29 reference statements)
12
132
2
7
Order By: Relevance
“…While understanding these isolate-specific, qualitative interactions provides valuable contributions to both applied and general understanding of plant defense, interest has grown in discovering the bases of ''partial'' or quantitative resistance, with the goal of developing durable resistance to diverse pathogens (Niks and Rubiales 2002). Naturally variable resistance to necrotrophic plant pathogens such as Botrytis cinerea, Alternaria brassisicola, Plectosphaerella cucurmerina, or Sclerotinia sclerotiorum appears to be quantitative and polygenic (Kim and Diers 2000;Micic et al 2004;Llorente et al 2005;Finkers et al 2007Finkers et al , 2008Maxwell et al 2007). However, the nature and extent of isolate-specific interaction between plants and necrotrophic pathogens is relatively unknown, and no qualitative naturally variable resistance genes effective against necrotrophic pathogens have been described ( Jones and Dangl 2006).…”
mentioning
confidence: 99%
“…While understanding these isolate-specific, qualitative interactions provides valuable contributions to both applied and general understanding of plant defense, interest has grown in discovering the bases of ''partial'' or quantitative resistance, with the goal of developing durable resistance to diverse pathogens (Niks and Rubiales 2002). Naturally variable resistance to necrotrophic plant pathogens such as Botrytis cinerea, Alternaria brassisicola, Plectosphaerella cucurmerina, or Sclerotinia sclerotiorum appears to be quantitative and polygenic (Kim and Diers 2000;Micic et al 2004;Llorente et al 2005;Finkers et al 2007Finkers et al , 2008Maxwell et al 2007). However, the nature and extent of isolate-specific interaction between plants and necrotrophic pathogens is relatively unknown, and no qualitative naturally variable resistance genes effective against necrotrophic pathogens have been described ( Jones and Dangl 2006).…”
mentioning
confidence: 99%
“…For that reason, this effect should be considered in the choice of screening methods or locations to be used in selecting superior genotypes for WM severity in the field. WM resistance in the field is a trait of complex inheritance, which includes physiological resistance and disease avoidance (Fuller et al 1984, Schwartz et al 1987, Kim and Diers 2000, Kolkman and Kelly 2002, Miklas et al 2013). In general, WM avoidance is associated with morphological and phenological traits, such as upright plant architecture, lodging resistance, canopy porosity and height, and maturity (Miklas et al 2013, Tivoli et al 2013, and these traits are highly influenced by the environment (Teixeira et al 1999, Miklas et al 2013, Moura et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that one or more of these factors can significantly reduce the intensity of white mold in soybean (Vidić 1982b, Boland & Hall 1987, Nelson et al 1991, Kim et al 1999. Genetic evidence for physiological resistance and avoidance mechanisms were defined by Kim & Diers (2000) in the process of mapping the three quantitative trait loci (QTL). Two loci control disease avoidance mechanisms and they are primarily associated with flowering time, plant height and lodging.…”
Section: Sclerotinia Sclerotiorummentioning
confidence: 99%